Colombia : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper examines the export growth in Colombia. Colombian exports are heavily concentrated in commodities but the large real depreciation since 2015 offers an opportunity to grow nontraditional exports substantially. Colombia's comparative advantage in noncommodity products was weak in 2013-15, and export diversification was low, partly owing to the commodity price boom. Exports grew moderately in recent years but in line with historical relationships given fundamentals. The export outlook is positive. Given global growth assumptions, the IMF staff's models predict acceleration in export growth. The historical experience of commodity exporters suffers large real depreciations also paints a positive picture.